Food safety management systems (FSMS) in the dairy industry: A review - Bintsis, Thomas; Papademas, Photis (My University, 2010)
Food safety management systems in the industry have been designed and established over the last four decades with several revisions. The dairy industry soon realised the need for proactive procedures hence implementing HACCP (Hazard Analysis and Critical Control Points) for ensuring that safe dairy products would reach the consumers. This article reviews the food safety management systems as well as the relevant EC Regulations that are currently implemented by the dairy industry. The need for rigorous controls in the dairy industry is also highlighted
Keywords: Dairy products industry; Dairying; Food safety issues; Hazard Analysis and Critical Control Point (Food safety system); Milk; Dairy products